SIKAP MASYARAKAT DESA SUNGAI NILAM TERHADAP PENEBANGAN KAYU TANPA IZIN (STUDI KASUS DI DESA SUNGAI NILAM KECAMATAN JAWAI KABUPATEN SAMBAS) - Suryadi, Andi; Zainal, Sofyan; Muin, Sudirman (Universitas Tanjungpura, 2016)
Sungai Nilam village at Jawai Subdistrict of Sambas Regency has high potential of nature, such as forest products (timber) and non-timber forest products such as rattan, bamboo, honey and others. The forest has been the source of the community, because community a lot of activity in the forest such as rattan, bamboo and other activities. But the Illegal logging activity has indirectly damaging natural resources at Sungai Nilam village the forest. The purpose of study was to determine the attitude of the community in Sungai Nilam Village against illegal logging in their village and to determine the relationship of each of these factors: perception, knowledge, income, and cosmopolite and community interaction with public attitudes towards forest of Sungai Nilam village against illegal logging. Research was conducted on March 2016 with survey method descriptively with interview technique. The samples were collected by purposive sampling and the numbers of respondents are 94. The result of the research showed that 48 respondents (51.10%) belonging to the group of receive and high attitude on illegal logging, meanwhile 46 respondents (48.90 %)belong to a neutral stance. No one has refused or rejected the illegal logging activity in their village.This is because in the reality the community is dependent upon the results of forest timber and non-timber forest products in their everyday lives. It is needed the support from the government to their livelihood to overcome the illegal logging activity in their village. Keywords: attitude, illegal logging, Sungai Nilam village